Lipid droplet hijacking by intracellular pathogens. (21st November 2016) - Roingeard, Philippe; Melo, Rossana C.N.
Abstract: Lipid droplets were long considered to be simple storage structures, but they have recently been shown to be dynamic organelles involved in diverse biological processes, including emerging roles in innate immunity. Various intracellular pathogens, including viruses, bacteria, and parasites, specifically target host lipid droplets during their life cycle. Viruses such as hepatitis C, dengue, and rotaviruses use lipid droplets as platforms for assembly. Bacteria, such as mycobacteria and Chlamydia, and parasites, such as trypanosomes, use host lipid droplets for nutritional purposes. The possible use of lipid droplets by intracellular pathogens, as part of an anti‐immunity strategy, is an intriguing question meriting further investigation in the near future.